The Relationship Between Business Ethics and Distribution Channels in Efforts to Increase Sales Volume at CV Aneka Jaya - Ammar Abdillah s (Manajemen Multitalenta Indonesia, 2026)
This study aims to examine the implementation of business ethics and the effectiveness of distribution channels in influencing sales volume at CV Aneka Jaya Malang. The study was motivated by a decline in sales volume from 90% in 2023 to 80% in 2024 and 70% in 2025, despite the company’s consistent application of ethical business practices and its established relationships with business partners. This study employed a descriptive qualitative approach using a single case study design. Data were collected through structured interviews, direct non-participant observation, and documentation involving the company’s President Director, Operations Manager, and representatives of three partner stores. Data validity was ensured through source triangulation, technique triangulation, and member checking. The findings indicate that business ethics, particularly honesty, transparency, fair pricing, product responsibility, effective complaint handling, and integrity in partnership relationships, contribute significantly to maintaining partner trust, customer loyalty, and purchase intentions. However, ethical practices alone were insufficient to sustain sales volume when distribution operations encountered technical constraints. The study found that aging delivery vehicles, traffic congestion, extreme weather, and delivery delays frequently caused product shortages at partner stores, resulting in missed sales opportunities. Meanwhile, the company’s centralized distribution system, inventory control, FIFO stock rotation, minimum stock thresholds, and the use of Transportation Management System (TMS) and GPS technologies supported product availability and distribution efficiency. The study concludes that business ethics and distribution channels play complementary roles in sustaining sales performance. Business ethics create trust and purchase intentions, while reliable distribution converts these intentions into actual transactions. Therefore, improving fleet reliability and digital inventory management is essential for restoring and strengthening sales volume sustainability.